Relationship of companies’ characteristics to foreign ownership: Studies on emerging market stock exchange in seven countries from ASEAN and Middle East - Arsya, Riz Zaidan Febriano; Arfinto, Erman Denny (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study explores the relationship between company’s characteristics and foreign ownership within the emerging market stock exchanges from 7 countries in the ASEAN and Middle East. The objective is to provide an understanding of determinants that influence foreign investors to invest in companies in emerging markets. This study uses panel data of publicly traded companies from Philippines, Thailand, Indonesia, Vietnam, UAE, Saudi Arabia, and Qatar within Q3 2020 – Q4 2022 period with the econometric robust regression model approach. Employing a quantitative research approach, this study utilizes a robust regression analysis. Various company characteristics, such as size, profitability, liquidity, leverage, dividend yield, and book-to-market value, are examined as potential determinants of foreign ownership. Results show that size has strong significant positive relationship to foreign ownership, profitability has positive not significant relationship to foreign ownership, liquidity has positive not significant to foreign ownership, leverage has negative weak significant to foreign ownership, dividend yield has positive significant to foreign ownership, and book-to-market has positive moderate significant to foreign ownership. The findings contribute to a deeper understanding of foreign ownership dynamics within the emerging market stock exchanges in the ASEAN region and Middle East, providing a solid foundation for informed decision-making and strategic planning.